Crowd-centric Requirements Engineering - Snijders, Remco; Dalpiaz, Fabiano; Hosseini, Mahmood; Shahri, Alimohammad; Ali, Raian (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
Requirements engineering is a preliminary and crucial phase for the correctness and quality of software systems. Despite the agreement on the positive correlation between user involvement in requirements engineering and software success, current development methods employ a too narrow concept of that user and rely on a recruited set of users considered to be representative. Such approaches might not cater for the diversity and dynamism of the actual users and the context of software usage. This is especially true in new paradigms such as cloud and mobile computing. To overcome these limitations, we propose crowd-centric requirements engineering (CCRE) as a revised method for requirements engineering where users become primary contributors, resulting in higher-quality requirements and increased user satisfaction. CCRE relies on crowd sourcing to support a broader user involvement, and on gamification to motivate that voluntary involvement.